Variation in biotic and abiotic factors associated with white spot syndrome virus (WSSV) outbreak in shrimp culture ponds - Swathi, A.; Shekhar, M. S.; Karthic, K.; Vinaya Kumar, K.; Muralidhar, M.; Hauton, Chris; Vijayan, K. K. (Indian Journal of Fisheries, 2021)
Shrimp production in India has gradually increased since 2009 with the introduction of Penaeus vannamei. Most coastal states in India have been important contributors to P. vannamei  production. However, among the many challenges faced in sustainable shrimp farming, prevention of viral diseases and pond water quality management remain major concerns. In this study, 27 shrimp ponds located in Kalpakkam and Elavur regions of Tamil Nadu were monitored to characterise the pond water parameters including pH, salinity, temperature, alkalinity, ammonia, nitrite, hardness, dissolved oxygen (DO) and Vibrio spp. load. Sudden outbreaks of white spot syndrome virus (WSSV) were observed in some ponds  which were found to be associated with variations in abiotic parameters. Parameters such as pH, DO and nitrite were observed to be within the permissible range, while temperature, salinity, Vibrio spp. load and ammonia were  relatively higher in certain ponds. The influence of these abiotic factors triggering WSSV outbreak were investigated  in this study.Keywords: Aquaculture, Penaeus vannamei, Vibrio spp., Water parameters, White spot syndrome virus